Nutritional intake and anthropometric changes of professional road cyclists during a 4-day competition - Sanchez-Munoz, C.; Zabala, M.; Muros, J. J. (Scandinavian Journal of Medicine & Science in Sports, 2016)
Appropriate nutrition through adequate dietary intake of total calories, macronutrients, and micronutrients is an essential component of optimizing the performance of all elite athletes. The aim of this study was to describe the food intake, body composition, and biochemical profile of professional cyclists during the Tour of Andalusia, a four-stage race covering a total distance of 647.6 km. Nutritional data were collected by trained investigators who weighed all of the food and fluid ingested by the cyclists. The nutritional intake of the cyclists was as follows: CHO, 12.8 ± 1.7 g/kg of body weight (BW; 62.3%); fat, 2.1 ± 0.2 g/kg BW (23.2%); proteins, 3.0 ± 0.3 g/kg BW (14.5%); total kcal was 5644.3 ± 593.1. Intake of all micronutrients, except for folate and potassium [which were 93.7% and 91.3% of Recommended Dietary Allowances (RDA)] exceeded the RDA/I. Percentage of body fat and fat weight significantly decreased (P < 0.05) while weight of muscle mass remained unchanged after the Tour. Concentrations of urea, aspartate aminotransferase, alanine aminotransferase, creatine kinase, myoglobin, and high-density lipoproteins significantly increased (P < 0.05) after the Tour. To our knowledge, this is the first study to describe both nutritional intake and the body and biochemical composition of a sample of professional road cyclists during a top-class cycling race.